Active Labour Market Programmes in Poland Between 2005 and 2010; Programy aktywnej polityki rynku pracy w Polsce W latach 2005-2010 - Walentyna Kwiatkowska (Comparative Economic Research. Central and Eastern Europe, 2013)
High unemployment in Poland is a major socio-economic problem. The unemployment rate in Poland reached the level of 16.7% in 2005, 9.3% in 2010 and 9.7% in 2011. Unemployment in Poland is mainly structural, which is reflected in the structural imbalances between labour demand and labour supply with respect to vocational qualifications, professions, and spatial deployment. The main factor determining unemployment is the necessity for structural changes in the Polish economy caused by its transformation and integration with the European Union, changes aimed at enhancement of economic innovation, competitiveness and effectiveness. An active labour market policy plays an important role in a situation characterized by high structural unemployment. Efficiently applied instruments of an active labour market policy can reduce this unemployment. Therefore, the main aim of this paper is to evaluate the role of the active labour market policy in Poland between 2005-2010, taking into consideration the characteristics of its main instruments, its participants, and expenditures. – – W warunkach wysokiego strukturalnego bezrobocia w Polsce wazṅa role w jego zwalczaniu odgrywa aktywna polityka panśtwa na rynku pracy. Strukturalny charakter bezrobocia wynika z niedopasowania struktury podazẏ pracy do struktury popytu na prace w aspekcie kwalifikacyjnym, zawodowym i przestrzennym. Bezrobocie to jest głoẃnie determinowane koniecznosćia przemian strukturalnych w polskiej gospodarce dla poprawy jej innowacyjnosći, konkurencyjnosći i efektywnosći jako panśtwa członkowskiego Unii Europejskiej. Podstawowym celem opracowania jest ocena skutecznosći aktywnej polityki rynku pracy w zwalczaniu bezrobocia w Polsce w latach 2005-2010. Realizacja tego celu wymaga dokonania charakterystyki instrumentoẃ tej polityki oraz usług urzedoẃ pracy w procesie aktywizacji zawodowej bezrobotnych, ukazania wydatkoẃ na realizacje aktywnej polityki rynku pracy oraz uczestnikoẃ programoẃ aktywnych, ktoŕzy dzieki nim uzyskali zatrudnienie. Podjeta jest takzė ocena efektoẃ zatrudnieniowych i kosztowych zwiazana ze stosowaniem aktywnej polityki rynku pracy.
Keywords: 330